Importance of Higher Order Thinking Skills (HOTS in Academic Research Writing): A Structured Literature Survey - Kareem, Mustafa Nasser Abdul (South Asian Journal of Social Sciences and Humanities, 2022)
The aim of this paper is to explore how postgraduate students can master higher order thinking skills (HOTS) in academic research writing (ARW) by reviewing other research studies. It also aims to determine how the elements of HOTS such as analysing, synthesizing, and evaluating are important for the courses in academic communities. To achieve this purpose, the paper will explore pedagogical strategies as enlisted in the literature for enhancing students’ skills in academic research writing based on HOTS. Therefore, the findings would provide writing educators with comprehensive overview on how postgraduate students are fully prepared for the advanced tasks of academic research writing.
Keywords: higher order thinking skills; Academic research writing (ARW); Tertiary educational level; Postgraduate students; Effective strategies